A Prospective Evaluation of the Effects of the COVID-19 Pandemic on Youth with Primary Headache Disorders - Mark Connelly; Jennifer Dilts; Madeline Boorigie; Trevor Gerson (Children, 2023)
Alterations in certain academic and social/family routines during the COVID-19 pandemic have been speculated to be either a risk factor or buffer for poor health outcomes for youth with stress-sensitive health conditions such as primary headache disorders. The current study evaluated patterns and moderators of pandemic impacts on youth with primary headache disorders, with an aim of extending our understanding of the relationship between stress, resilience, and outcomes in this population. Children recruited from a headache clinic in the midwestern United States reported on their headaches, schooling, routines, psychological stress, and coping at four timepoints ranging from within a few months of the pandemic onset to a long-term follow-up 2 years later. Changes in headache characteristics over time were analyzed for association with demographics, school status, altered routines, and stress, and coping. At baseline, 41% and 58% of participants reported no change in headache frequency or intensity, respectively, relative to pre-pandemic levels, with the remainder almost equally divided between reporting an improvement or worsening. The results of multilevel growth model analyses indicated that headache intensity remained more elevated over time since the start of the pandemic for respondents whose stress scores were relatively higher (b = 0.18, t = −2.70, p = 0.01), and headache-related disability remained more elevated over time for older respondents (b = 0.01, t = −2.12, p = 0.03). The study results suggest, overall, that the outcomes of primary headache disorders in youth were not systematically altered by the COVID-19 pandemic.